If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2n-8=n+n-4-4
We move all terms to the left:
2n-8-(n+n-4-4)=0
We add all the numbers together, and all the variables
2n-(2n-8)-8=0
We get rid of parentheses
2n-2n+8-8=0
We add all the numbers together, and all the variables
=0
n=0/1
n=0
| 6(-7x-1)=-300 | | 2(-1x+2)=-14 | | 4w-2+4(2w+4)=-2(w+1) | | -33.104+0.6r=3.4(1-1.2r) | | 3(2+3x)=-2(x-2-)-8 | | 2x-4+4=14 | | 15/20=z/10 | | (h÷6)-1=-3 | | 4-3b=6b-7 | | 6x+13+14x+33=180 | | 7/3=p-4/9 | | 6.80+.9x=7.30+.65x | | 6x-x=95 | | 0.35+0.6=0.1x+1 | | x(10+2=) | | 7X1/3=p-(4/9) | | 180-117=x | | 90/250=x/100 | | 3(2x-2)=2(x-3)+4x | | -3=(8h+3h)=5h+4 | | 6.25x=60+3.25x | | 90-14=x | | 29=-6(2n-9) | | y^2+10y–2=0 | | -3y-4y+8=8-7y-12 | | 90-35=x | | 25-8c=-15 | | 10m-7=-2m+41 | | r18-11=25 | | 8x-58-2x+35-2x+35=180 | | 12x-15=6x+36 | | -2z-19=11 |